Psychosocial Experiences of Colorectal Cancer Patients with Stoma - Riri Maria; Debie Dahlia; Dikha Ayu Kurnia (Indonesian Journal of Global Health Research, 2025)
The formation of a stoma impacts various aspects of a patient's life, including physical, psychosocial, and spiritual well-being. If these impacts are not properly managed, it could decline the patient's quality of life. This study aimed to explore the psychosocial experiences of colorectal cancer patients living with a stoma. Method: twenty participants were interviewed using semi-structured questions, and the data was analyzed using a phenomenological approach. the findings revealed three key themes: emotional reactions having a stoma, limited social interactions, and worries about performing religious practices. Based on these results, the study recommend the need for education for colorectal cancer patients with stomas, particularly psychosocial aspects, to improve adaptation and quality of life.